The Impact of Artificial Intelligence on Changes in Students Academic Indonesian Writing Styles - Meksi Rahma Nesti; Desi Afrianti; Apri Pendri (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
The rapid advancement of artificial intelligence technology has significantly impacted the academic writing practices of university students. This study aims to analyze the effect of artificial intelligence applications on changes in students' academic Indonesian writing styles. This research employed a qualitative descriptive approach, utilizing data collected from student assignments, digital writing samples, and interviews with university students. The findings reveal that artificial intelligence affects sentence structure, diction selection, coherence patterns, and academic writing efficiency. Students tend to produce more systematically structured texts; however, several writings demonstrate a decline in originality and critical elaboration. Furthermore, artificial intelligence increases students reliance on instant writing assistance tools. The results indicate that integrating artificial intelligence into academic writing necessitates digital literacy and critical language awareness to preserve originality and academic integrity. This research contributes to the advancement of digital linguistics and academic writing studies in higher education.